The Topography of Corporal Relics in Twelver Shiʿism: Some Anthropological Reflections on the Places of Ziyāra - Parsapajouh, Sepideh (Journal of Material Cultures in the Muslim World, 2021)
Because of the plurality of the venerated figures, the holy places of Twelver Shiʿism are numerous. This paper focuses on places of devotion that are supposed to contain bodily relics and presents them in a schematic framework to discuss the importance of some of these places, and some aspects of their transformations over time. I first identify the sacred figures of Shiʿism and the place or the places (multi-locality of tombs) attributed to each of them. I then move on to a discussion of two things that can seem paradoxical, i.e. the immateriality of the sacred figure, and his/her omnipresence beyond places. My findings are based on field observations and interviews, and on documentary and published sources.